What Have We Learnt About the Sourcing of Personal Protective Equipment During Pandemics? Leadership and Management in Healthcare Supply Chain Management: A Scoping Review - Best, Stephanie; Williams, Sharon J. (Frontiers in Public Health, 2021)
Introduction: During the ongoing COVID-19 pandemic there have been much publicised shortages in Personal Protective Equipment (PPE) for frontline health care workers, from masks to gowns. Recent previous airborne pandemics provide an opportunity to learn how to effectively lead and manage supply chains during crisis situations. Identifying and plotting this learning against time will reveal what has been learnt when and, significantly, what can be learnt for the future. Aims: i) To identify the temporal trajectory of leadership and management learning in health supply chain management through pandemics and ii) ii) to identify leadership and management lessons to enable the resilient supply of key items such as PPE in future pandemics. Methods: We undertook a scoping review in line with PRISMA (scoping review extension) searching Business Source Premier, Health Business Elite, Medline, ProQuest Business Collection and PubMed. Search terms were focused on recent airborne pandemics. Titles and abstracts were downloaded to Endnote and duplicates removed. Two authors independently screened the titles and abstracts. Inclusion criteria focused on leadership and management in health supply chains during pandemics, peer reviewed or grey literature: exclusion criteria included not in English and not focused on a named pandemic. A data extraction tool was designed to capture findings from the final articles. Results/Discussion: We found 92 articles and, after screening, included 30 full text articles. The majority were focused on COVID-19 (N=27). We identified four themes i) Leadership and management learning for pandemic PPE supply chain management, ii) Inhibitors of PPE supply chain resilience during a pandemic, iii) Facilitators employed to manage the immediate impacts of PPE supply chain demands during a pandemic and iv) Facilitators proposed to ensure longer term resilience of PPE supply chains during pandemics Our study suggests there has been limited leadership and management learning for PPE supply chains from previous pandemics, however there has been extensive learning through the COVID-19 pandemic. Resilience of PPE supply chains was reported to be interdependent on i) sustainability, ii) the practice of PPE and iii) long term environmental impact of PPE suggesting the need, long term, to move to a circular economy approach.